Development of Problem-Based Learning E-Module for Grade X High School Students : Preliminary Research - Danti Aulia Sari; Nurkhairo Hidayati (Lombok Institute, 2024)
This study aims to determine the initial needs related to teaching materials and the learning models used in the learning process. The research method employed is quantitative descriptive research. This study represents the preliminary stage of development research. The data collection instruments for this research include interview sheets, teacher-needs questionnaires and student-needs questionnaires. The developed learning materials take the form of e-modules, which may consist of text, images, and instructional videos as a structured approach to independent learning. A needs analysis is conducted to identify the learning resources teachers utilize, learning obstacles, and the learning resources students require. The population for this study comprises Grade X students, with a sample size of 42 students and one biology teacher. The data obtained are analyzed using descriptive statistical analysis. The needs analysis results indicate that 79.66% of the 42 Grade X students require e-modules to support the learning process. Therefore, it is necessary to develop teaching materials like e-modules integrated with the Problem-Based Learning (PBL) model to enhance the learning experience.